An image inpainting method based on weighted priority and classification matching - Yan CAO; Wei JIN; Randi FU (Dianxin kexue)
The calculation of the priority of the pixel to be repaired and the determination of the best matching block are based on two basic steps of the texture synthesis image inpainting method.The traditional method is not suitable because it is difficult to determine the confidence in the priority calculation,and it is difficult to search for the best matching block.An image inpainting method based on weighted priority and classification matching was proposed.In the priority model,the exponential function and the normalization function were introduced to optimize the confidence and data items separately,the further benefit of which was a more objective priority of calculation and a more reasonable repair order.Based on the proposed functions,the structure information was used as a measure factor of the search matching block,and the best matching block was selected by the classification and screening method.Experimental results show that the proposed method can shorten the repair time under the condition of obtaining good repair effect.